ANALISIS PENGARUH E-WOM, PEMASARAN DIGITAL DAN KUALITAS KONTEN MEDIA SOSIAL TERHADAP BRAND AWARENESS - Victor Lamboy Sinaga; Vivid Violin; Mozart Malik Ibrahim; Fildzah Shabrina; Ratu Nadya Wahyuningratna; Ilham Arief (POLITEKNIK LP3I JAKARTA, 2025)
This study investigates the impact of electronic word-of-mouth (e-WOM), digital marketing, and social media content quality on brand awareness. A quantitative approach was employed, utilizing a questionnaire survey of 100 consumers. Multiple linear regression analysis revealed a significant and positive relationship between each independent variable (e-WOM, digital marketing, and social media content quality) and the dependent variable (brand awareness). The findings suggest that company management should adopt strategic measures to enhance brand image, thereby fostering positive e-WOM. This can be achieved by consistently maintaining and improving product quality, increasing product reliability through strengthened production and logistics systems, and providing excellent after-sales service.